Predicting delirium in post-anaesthesia recovery: a retrospective analysis and validation of a nomogram model for patients undergoing benign biliary surgery - Wu, Li-jun; Song, Teng; Li, Li (Journal of the Pakistan Medical Association, 2025)
This study aimed to develop a nomogram for predicting post-anaesthetic delirium in patients who underwent benign biliary surgery under general anaesthesia. We retrospectively analysed 460 patients from March 2019 to March 2023 using IBM SPSS Statistics 26.0 and R 4.2.3, identifying predictors of delirium through logistic regression. Notable predictors included anaesthetic dosage, extubation time, post-anaesthesia care unit (PACU) duration, and American Society of Anaesthesiologists (ASA) classification > 2. The developed nomogram demonstrated high predictive accuracy, with an area under the curve (AUC) of 0.881 in the training set and 0.828 in validation. This tool provides clinicians with reliable pre-operative risk assessment capabilities. Keywords: General anaesthesia, Biliary surgery, Post-operative delirium, Nomogram model.